Production of extracellular polysaccharases by the marine protists, thraustochytrids, with special reference to α-Amylase activity - PRIYANKA V. SHIRODKAR; USHA DEVI MURALEEDHARAN; SESHAGIRI RAGHUKUMAR (International Journal of Pharma and Bio Sciences, 2017)
Thraustochytrids, a once obscure group of straminipilan protists, are now increasingly coming into the limelight by virtue of the diverse industrial potential of their cell products which include polyunsaturated fatty acids (PUFAs) and hydrolytic enzymes. The present study dwells on production of extracellular polysaccharide-degrading enzymes by isolates from various coastal and mangrove habitats of Goa. Extensive screening has yielded strains that produce enzymes with multiple hydrolytic activities and potential in diverse industrial applications. They produced a plethora of enzymes that included agarases, amylases, pectinases, chitinases and carrageenases, many of which appeared to be secreted constitutively. Agarase and amylase activities predominantly observed in most isolates from mangrove habitats had special characteristics that would favor commercial applications. This therefore stands as the first detailed report on extracellular amylase production by thraustochytrids. Amylases produced by two isolates, viz., TZ (ATCC#PRA-295) and AH-2 (ATCC#PRA296) were confirmed to be α-amylases, enzymes of great significance in present day biotechnology.